Oxygen isotopes as a tool to quantify reservoir-scale CO2 pore-space saturation. (August 2017) - Serno, Sascha; Flude, Stephanie; Johnson, Gareth; Mayer, Bernhard; Karolytė, Rūta; Haszeldine, R. Stuart; Gilfillan, Stuart M.V.
Highlights: First comprehensive review of oxygen isotope data from global CO2 injection projects. Assessing the use of oxygen isotopes to quantify CO2 pore-space saturation. Oxygen isotope ratio of water in contact with free-phase CO2 changes predictably. Summary of available information on the oxygen isotope composition of captured CO2 . Abstract: Structural and residual trapping of carbon dioxide (CO2 ) are two key mechanisms of secure CO2 storage, an essential component of Carbon Capture and Storage technology. Estimating the amount of CO2 that is trapped by these two mechanisms is a vital requirement for accurately assessing the secure CO2 storage capacity of a formation, but remains a key challenge. Here, we review recent field and laboratory experiment studies and show that simple and relatively inexpensive measurements of oxygen isotope ratios in both the injected CO2 and produced water can provide an assessment of the amount of CO2 that is stored by residual and structural trapping mechanisms. We find that oxygen isotope assessments provide results that are comparable to those obtained by geophysical techniques. For the first time we assess the advantages and potential limitations of using oxygen isotopes to quantify CO2 pore-space saturation based on a comprehensive review of oxygen isotope measurements from reservoir waters and various global CO2 injection test sites. We further summarise the oxygen isotope composition of captured CO2 in order to establish the controls on this fingerprint.